Capital structure decisions: Empirical evidence from Albanian non-financial companies - Xhori, Elvis (Edelweiss Applied Science and Technology, 2024)
Well-structured existing companies need continuous sources of financing from the moment of creation until their continuation, to finance growth in sustainable assets and, above all, the value of their shares. Understanding the capital structure helps managers create the optimal capital structure for the company. The capital structure of firms is an important research area in corporate finance and remains at the center of studies by various academics. However, most studies have focused on listed companies in developed countries, and little attention has been paid to unlisted firms in developing countries, such as Albania. This study aims to bridge the gap between decision-making management and its financial effectiveness by analyzing the capital structure of unlisted companies in Albania. The proposed research question is “what are the main factors influencing the capital structure decision of non - financial companies in the Tirana region?” Based on previous studies, this paper examines several of the main factors (determinants) that are believed to reliably influence the capital structure. The specific key factors analyzed in this study are: Performance, Asset tangibility, Company liquidity, Company size, financial flexibility, Tax benefits from non-debt expenses, Growth opportunities, Company age, and the one period lagged debt ratio. We focus our study unto 75 non - financial companies of Albania for years to 2019 – 2023, and by calculating variables to measure capital structure, we run multiple regression analysis. We use total - debt, long - term debt and short-term debt to measure capital structure. The results of the study will be confirmed through analysis of empirical models and other statistical measurements. The linear regression model of multiple variables will be tested using three econometric techniques: POLS, FEM, and REM. The results indicate that lagged debt ratio of TD, LTD, STD, ROA, ROE, growth opportunity and liquidity are statistically significant and support for the pecking order theory (POT). The results show that firms do not have an optimal capital structure, but they had an average of 55.73 percent total-term debt, 15.27 percent long-term debt and 40.46 percent short-term debt. Trade-off theory which argues that firms increase the level of debt to take benefit from the deduction of debt interest before tax is not applicable in Albania. These findings contribute to the existing literature on the relationship between capital structure and decision making and give hints to more profitable ways of financing for these companies such as relying on long-term financing and not only on short term or finding alternative ways in equity financing.